3D curves with a prescribed curvature and torsion for an aerial robot. (27th September 2011) - Bestaoui, Yasmina
The objective of this paper is to generate a desired flight path to be followed by an aerial robot. A curve with discontinuous curvature and torsion is not appropriate for smooth motions for any vehicle architecture. The flyable path should be smooth, i.e. without twists and cusps. The smoothness of the path is determined by amount of bending of the path, measured by curvature and torsion of the path. Three different classes of curves are presented. First, constant curvature and torsion followed by a linear variation versus the curvilinear abscissa then a quadratic variation. Finally, the problem of manoeuvre between two trim helices of different curvature and torsion is tackled.